Combined QSAR/QSPR and molecular docking study on fluoroquinolones to reduce biological enrichment. (April 2019) - Zhao, Xiaohui; Zhao, Yuanyuan; Ren, Zhixing; Li, Yu
Graphical abstract: Highlights: The log K ow values of 29 compounds were analyzed with 3D-QSAR method. The electropositive or hydrophobic groups could decrease the log K ow values. The 23 derivatives all had lower biological enrichment than nadifloxacin. The mechanisms of the FQs with Gram-negative/positive bacteria were evaluated. Abstract: With the aim of reducing the adverse effects of fluoroquinolones in the environment, a complete design and screening system for the low biological enrichment and high photodegradabilities of 29 fluoroquinolones was established through a three-dimensional quantitative structure–activity relationship (3D-QSAR) model and molecular docking. The interaction mechanisms of the fluoroquinolones with Gram-negative bacteria (DNA gyrase in Escherichia coli) and Gram-positive bacteria (Topoisomerase IV in Staphylococcus aureus) were also evaluated. Consequently, the 3D-QSAR model showed that the 3- and 18-positions of the fluoroquinolones strongly affected their biological enrichment, and that the introduction of electropositive or hydrophobic groups at these positions reduced the logarithm of the octanol-water partition coefficient. Using nadifloxacin as a template, 23 derivatives with lower biological enrichment than nadifloxacin (decreased by 30.12%–94.18%) were designed. Meanwhile, the photodegradabilities of 15 derivatives were increased compared with nadifloxacin. Finally, the further screening by molecular docking of nadifloxacin and the above 15 derivatives with DNA gyrase and Topoisomerase IV showed that 13 of the derivatives had lower biological enrichment (decreased by 0.30%–16.76%) than nadifloxacin in the bacteria.